UJI VALIDITAS APLIKASI SI-BOOK MENGGUNAKAN SPSS DENGAN KOMBINASI METODE R-TABEL DAN COHEN’S KAPPA - Putra Dwi Wira Gardha Yuniahans; Rizky Parlika; Rayhan Saneval Arhinza; Vito Fausta Majid; Muhammad Ghifari Alifian (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
Validity is a measure to show the level of validity or validity of an instrument. An instrument is said to be valid if it is able to measure what the user wants and is able to obtain the right data from the variables studied. Validity is the accuracy or accuracy of an instrument to measure what is to be measured. The researcher used SPSS with the R-Table method and Cohen's Kappa for testing the validity of the software. In testing data collection instruments, validity can be divided into 2, namely item validity and factor validity. The measurement of factor validity correlates the item scores with the total item scores. In validity testing, 30 people will collect sample data, then the data will be processed using SPSS by applying the R-Table method, while Cohen's Kappa is used to measure the degree of agreement of two raters in classifying objects into groups / groups and Measuring agreement on alternative new methods with existing methods